Experimental study on the dust control performance of rotating fog curtain under the perturbation of long-pressure and short-pumping ventilation - Jingxu Chen; Yongkai Zhi (Scientific Reports, 2024)
Abstract The dust source point in the coal-breaking operation prolonged activities generate substantial dust, diminished the air quality at the tunneling face. This study focuses on the pneumatic vortex fog curtain dust control system in the underground coal mine tunneling face. It explores the dust-trapping performance of this system under the disturbance of a long-pressure and short-suction auxiliary ventilation system. The results indicate that the respiratory dust captured by the fog curtain wall on the driver’s working side can be reduced from an average concentration of 135.5 mg/m3 to 2.5 mg/m3, and on the 15 m downwind side of the coal-cutting machine, it decreases from 70.2 mg/m3 to 2.5 mg/m3. Under the disturbance of the long-pressure and short-suction ventilation system, as the wind speed increases, the rotating fog curtain gap expands, reducing the sealing performance. Without compromising the fog curtain conditions, this combined system achieves efficient dust suppression, significantly improving the working environment at the tunneling face.